Ehlers-Danlos Syndrome – an underdiagnosed condition - Cumarasamy, Rubini; Mohd Hanafi, Mohd Sharil Iman; Che' Man, Mohamad (2019)
Failure to thrive is a common clinical presentation discovered during continuity of child care at primary care clinic1. The causes of failure to thrive are multifactorial which a challenge becomes in diagnostic process. Hence, the pitfall arises when there are overlapping causes whereby nutritional and psychosocial issues mask the suspicion of medical cause [1]. A well-looking child with failure to thrive is probably considered as normal variants of growth or having nutritional deficiency [2]. We highlighted a case report of a 4 years 9 month-old girl with red flag of failure to thrive who was recently diagnosed to have Ehlers-Danlos Syndrome Hypermobility type based on manifestation of classical signs with a positive Beighton score of eight [3]. She had unresolved failure to thrive after birth despite intervention, with all anthropometric criteria below expected for age and gender. Otherwise, she was asymptomatic and developmentally-age-appropriate. These provide a clue to evaluate for a pathological condition which leads to discovery of this undiagnosed syndrome. Even though there is no cure for Ehlers-Danlos Syndrome, a correct diagnosis helps for appropriate treatment plan to monitor potential complications and provide genetic counselling for the family [3].